Ecofriendly densitometric RP-HPTLC method for determination of rivaroxaban in nanoparticle formulations using green solvents. Issue 4 (10th January 2020) - Alam, Prawez; Ezzeldin, Essam; Iqbal, Muzaffar; Anwer, Md. Khalid; Mostafa, Gamal A. E.; Alqarni, Mohammed H.; Foudah, Ahmed I.; Shakeel, Faiyaz
Abstract : A literature survey revealed no suitable "reversed phase-high performance thin layer chromatography (RP-HPTLC)" method for the analysis of rivaroxaban in nanoparticle (NP) formulations. Abstract : A literature survey revealed no suitable "reversed phase-high performance thin layer chromatography (RP-HPTLC)" method for the analysis of rivaroxaban in nanoparticle (NP) formulations. Therefore, a novel rapid, simple, economical and environment friendly RP-HPTLC method has been established for the quantification of rivaroxaban in NP formulations and commercial tablets. RP-HPTLC analysis of rivaroxaban was performed using "RP-18 silica gel 60 F254S HPTLC plates". The binary mixture of green solvents ethanol : water (7 : 3 v/v) was utilized as the mobile phase. The quantification of rivaroxaban was carried out in densitometric mode at λ max = 253 nm. Rivaroxaban peaks from NP formulations was confirmed by comparing its single spot at R f = 0.71 ± 0.02 with that of the standard. The proposed RP-HPTLC method was found to be linear in the range of 50–600 ng per band with R 2 = 0.9994. The equation for linear regression analysis was obtained as Y = 13.28 x + 1189.4. The proposed RP-HPTLC technique was validated for "precision, accuracy, robustness and sensitivity". The accuracy of the method was obtained as 97.97–99.67%. The % RSD in repeatability and intermediate precision was recorded as 0.46–0.64 and 0.48–0.86%, respectively. The LOD and LOQ for rivaroxaban were obtained as 18.45 and 55.35 ng per spot, respectively. The % content of rivaroxaban in marketed tablets and NPs was recorded as 99.20 and 98.08%, respectively. The proposed RP-HPTLC technique could be successfully applied for the pharmaceutical assay of rivaroxaban in NPs, marketed tablets and related formulations.